Identification and characterization of drought-induced genes in Malaysia rice cultivars, MR220 and MR211 using RNA-sequencing platform - Othman, Tajul Ariffien (2019)
Drought is one of the abiotic stresses on plants, causing significant detrimental impacts, especially to lowland rice (Oryza sativa L.) ecosystems. In order to obtain new insights on osmotic stress in rice, a comparative study using a Next-Generation Sequencing platform was conducted to elucidate osmotic-responsive genes from two local Malaysian rice cultivars, namely the commercially available drought-tolerant MR220 and the drought-sensitive MR211. In the study, 21-day-old seedlings of MR220 and MR211 were exposed to 6% PEG 6000 for 24 hours, which produced osmotic stress that mimicked the drought condition. The samples were collected and total RNA were extracted. Two transcriptomic libraries were constructed from both rice cultivars using the Illumina HiSeq 2000 platform. A total of 77,964,138 and 92,699,454 raw sequence reads were generated from these libraries. From the expressed genes from both libraries, around 44, 902 genes have been found overlapping each other. Then, 8,095 and 2,081 gen have been found uniquely in MR220 and MR211, respectively. Based on the gene annotation of O. sativa, a total of 106 genes were identified as differentially and significantly expressed in drought-tolerant and drought-susceptible cultivars, and a total of 29 genes were categorized as unknown genes. From the 106 differentially expressed genes (DEGs), 14 genes were up-regulated, while another 92 were downregulated in MR220. Gene Ontology (GO) and KEGG analysis were conducted to obtain the functional and biological role of the differentially expressed genes. Six drought related genes were selected for validating the RNA-Seq analysis using semiquantitative PCR. The validation result showed four out of six DEGs followed the RNA-Seq analysis. Then, two genes were selected form six semi-quantitative analysis, HP and Thia genes were validated using real-time qRT-PCR. The result showed same expression with semi-quantitative PCR. Overall, this study gives further insight on rice defense mechanisms during osmotic stress at early stage.